2015
DOI: 10.1016/j.sbspro.2015.04.465
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Identity, Congruence of Interest and Coping Strategy on Decision Making

Abstract: Construction of identity and mechanisms with which it reaches vocational maturity lead adolescents to explore their interests and to make adequate choice. The objective of the contribution is to value the role of identity, congruence of interests and coping strategies as predictive variables to decision making. The research involved 350 students, attending the 4 th and the 5 th year of senior secondary schools. They completed Ego Identity Process Questionnaire, Self-Directed Search, General Decision Making Sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
(11 reference statements)
1
15
1
1
Order By: Relevance
“…In the sphere of research on decisional processes, the presence of individual differences constitutes a propensity to react in a given way in a specific context, and therefore they influence the modalities with which each individual makes choices in a relatively stable way. Nevertheless, although empirical studies 48 , 49 have shown that individuals tend to use a certain style more frequently than others, the research reported here shows that decisional styles, far from being rigid and unchangeable, are flexible and modifiable in response to specific situations.…”
Section: Discussioncontrasting
confidence: 73%
“…In the sphere of research on decisional processes, the presence of individual differences constitutes a propensity to react in a given way in a specific context, and therefore they influence the modalities with which each individual makes choices in a relatively stable way. Nevertheless, although empirical studies 48 , 49 have shown that individuals tend to use a certain style more frequently than others, the research reported here shows that decisional styles, far from being rigid and unchangeable, are flexible and modifiable in response to specific situations.…”
Section: Discussioncontrasting
confidence: 73%
“…According to the literature, individuals who manifest well-being develop satisfying relationships, and there is a significant correlation between measures of psychological distress and scores related to personal, relational, and job satisfaction. 37 , 38 The findings of the present study, as suggested by the fourth hypothesis, are in agreement here. The data show that the perception of confusion, depressive anxiety, and physical problems are negatively correlated with vigor and dedication in the working context.…”
Section: Discussionsupporting
confidence: 93%
“…Although well-being and psychophysical health of teachers have important implications on the health and well-being of their recipients, studies dedicated to these workers and their consequences on the metacognitive style are quite rare, particularly in Italy [47][48][49].…”
Section: Introductionmentioning
confidence: 99%